Konsep Jalan Kehidupan dan Kematian Menurut Kitab Didakhe Pasal 1-6 - Sesilina Gulo; Hendi Hendi (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. The book of Didache is a non-canonical book in the Bible, therefore, the teachings of the book are not widely known, discussed, and taught. However, the book contains deep morality teachings. This article aimed to explore the teachings in the book so that we can explain the concept of the path of life and death as it was taught in the Bible. The study was conducted by using a descriptive-analytical approach based on Alistair Stewart’s view in his book “On the Way Life and Death, Light or Darkness: Foundation Texts in The Tradition.” From this study, that the teachings of the Book of Didache help believers to have spirituality discipline and lead to holiness of life so that believers no longer live in sins that will lead to death.Abstrak. Kitab Didakhe bukanlah Kitab kanonikal dalam Alkitab, oleh sebab itu ajaran dalam Kitab tersebut tidak banyak diketahui, dibahas, dan diajarkan. Namun demikian, Kitab tersebut mengandung ajaran moral yang dalam. Tujuan dari penulisan artikel ini adalah untuk menggali ajaran dalam kitab tersebut yang dapat menjelaskan konsep jalan kehidupan dan kematian sebagaimana yang diajarkan dalam Alkitab. Kajian dalam artikel ini menggunakan pendekatan deskriptif-analitis dengan mendasarkan pada pandangan Alistair Stewart dalam bukunya“On The Way Life and Death, Light or Darkness: Foundation Texts In The Tradition.” Dari kajian tersebut diperoleh hasil bahwa ajaran Kitab Didakhe menolong orang percaya untuk mendisplinkan diri dalam spiritualitas serta menuntun kepada kekudusan hidup sehingga orang percaya tidak lagi hidup di dalam dosa yang akan mendatangkan kematian.